Brand Trust for Digital-Only Bank Brands: Consumer Insights From an Emerging Market - Tosun, Petek (ATLAS, 2020)
Financial services are increasingly evolving and moving towards digital service models. New technologies and the rapid diffusion of the internet are introducing new business models in the banking industry, by providing many alternatives for reaching and interacting with customers. One of the new banking business models is digital-only banking. Digital-only bank brands are servicing in digital platforms without providing any traditional branch services. However, in many countries, banks are still operating within conventional service models, so some changes in laws and regulations may be required to provide digital-only banking services. Besides such structural and institutional requirements, positive consumer attitudes toward working with digital-only brands are prerequisites for any brand to be successful in the highly competitive financial services market. Positive consumer attitudes are especially important in the digital- only banking context since preferring a bank brand with a large network of established branches is still essential for building brand trust for many customers. Therefore, financial services institutions need to have a deep understanding of consumer perceptions and the antecedents of brand trust regarding digital-only banking. This study aims to explore consumer motives and elements of building customer trust for a digital-only banking brand in an emerging market context. Consumer insights were obtained as a result of a pilot study, which included preliminary interviews with retail banking customers. The interviews have shown that trust is the core factor for bank preference. Digital-only brands have the risk of being perceived as untrustworthy. Positive word-of-mouth, clear procedures, reliable terms and conditions, having responsive and effective customer services teams, and solving customer complaints fast are stated as important points to build brand trust for digital-only brands. This exploratory study may provide a basis for future empirical studies. The findings will be beneficial for the policy- makers, marketing managers of financial services institutions, and researchers who want to understand customer expectations.
Keywords: Financial services; Brand trust; Digital-only banking; Services marketing